Quinoxaline: a new directing group for ortho C–H alkenylation / intramolecular ortho C–H cycloamination under open air leading to bioactive polynuclear N-heteroarenes1. Issue 86 (18th September 2015) - Sunke, Rajnikanth; Kumar, Vimal; Venkat Shivaji Ramarao, E. V.; Bankala, Ramudu; Parsa, Kishore V. L.; Pal, Manojit
<x xml:space="preserve">Abstract</x> A two-step strategy involving quinoxaline directed the ortho C–H alkenylation/intramolecular ortho C–H cycloamination afforded new PDE4 inhibitors.